Legal Protection and Enforcement of Securities Dilution by Issuers in the Technology Business Sector with Multiple Vot-ing Rights Stock Classification after Initial Public Offering (IPO) - Raisha Cantika Mutiara; Aurora Jillena Meliala; Heru Sugiyono (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the legal protections and enforcement mechanisms against securities dilution in technology‐sector issuers adopting multiple voting rights stock classifications following an initial public offering (IPO) under Indonesia’s Financial Services Authority Regulation No. 22/POJK.04/2021. It addresses two core issues: the adequacy of minority shareholder safeguards embedded within the regulatory framework and the nature and extent of share dilution experienced by existing investors in dual‐class structures. Employing a normative legal research design with a doctrinal approach, the analysis draws on primary sources including UU No. 40/2007, UU No. 4/2023, POJK 22/POJK.04/2021, issuer prospectuses, and PT GoTo Gojek Tokopedia’s 2022–2024 annual reports complemented by secondary literature and tertiary legal references. Findings reveal that POJK 22/POJK.04/2021 integrates quantitative limits (a 90 percent cap on aggregate superior voting rights), procedural safeguards (minimum 5 percent ordinary‐shareholder quorum and independent renewal approval), temporal constraints (10‐year sunset clause), and one‐share‐one‐vote requirements for critical corporate actions, alongside a novel graduated voting ratio system. The GoTo case study underscores persistent misalignment between cash‐flow and voting rights, marked by significant share price volatility and reliance on share buybacks rather than dilutive issuances. While the regulatory framework is comprehensive, its efficacy is contingent on robust enforcement, transparency of indirect ownership, and institutional maturity. Empirical evaluation of post‐IPO dilution events, minority litigation outcomes, and enforcement actions is recommended to assess real‐world impacts.